The fauna of tree-holes in relation to environmental factors - Kitching, RL (1969)
Water-filled tree-holes are one of a group of similar aquatic habitats found in or upon plants of various kinds. A study has been made of the holes found in the roots and branches of beech trees in Wycham Woods, Berkshire. The habitat has been described in terms of physical, chemical and biological characteristics, the numbers of the species of animal found in it have been recorded over a period of time and some attempt has been made top relate the numbers of animals present to the environmental factors measured.